STRATEGI PENGEMBANGAN AGRIBISNIS CABAI MERAH DIKAWASAN AGROPOLITAN KABUPATEN SERANG - Sulaeni Sulaeni; Aris Supriyo Wibowo (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
Development Strategy in the Serang Regency Agropolitan Area. The goal of this research is : (1) To research the income of red chili farming in the Serang Regency agropolitan area, (2) To analyze the factors of production costs that affect the income of chili farming in the Agropolitan area of Serang regency (3) To find out the strategy for developing red chili farming in the agropolitan area of Serang Regency..Research method that used was observation and data registration that analyzed was secondary data, got from interview result of farmer. According number of population at location was 100 farmers, so total population that taken was 30% from 100 farmers so total sample was 30 farmers.Method of analysis that used: (a) analysis of clean income was difference of gross income reduced total production cost. (b) analysis of linier regression multivariate to explain influence of cost variable of seed, fertilizer, pesticide, manpower, mulsa, towards net income. (c) SWOT analysis.Result of analysis shows that in one season chili farmer at agropolitan area of Serang regency income Rp. 53,881,058.84/hectare. This is due to the collaboration between elements of farmers, bureaucrats, entrepreneurs and supporting elements. Result of regression analysis in red chili farming research at agropolitan area of Serang regency was .Seeds, fertilizers, mulch, and labor are very influential on the income of red chili farming. If the measurement of 4 factors is not in accordance with the five farms, it can affect or decrease farmer's income. Based on the results of the SWOT analysis with the value indicated that the difference in opportunity and threat is 0.92, while the difference between strength and weakness is 0.82. Then the strategy of developing red chili in the Agropolitan area of Serang Regency is in quadrant I where it supports aggressive strategies that describe a very good situation because it has opportunities and strength, so that it can take advantage of existing opportunities, strategies that must be implemented are supporting aggressive growth policies. In supporting an aggressive growth policy the priority strategy that can be applied in the effort of developing agribusiness for chili farming in attacking agropolitan regency is to carry out the five farming strategies, planting using superior seeds and utilizing soil fertility and optimizing human resources so that production resources are limited and attacks plant disease organisms can be overcome.